Life, death and growing up on the western front - Fletcher, Anthony (New Haven : Yale University Press, 2013)
"This book was inspired by the author's discovery of an extraordinary cache of letters from a soldier who was killed on the Western Front during the First World War. The soldier was his grandfather, and the letters had been tucked away, unread and unmentioned for many decades. Intrigued by the heartbreak and history of these family letters, Fletcher sought out the correspondence of other British soldiers who had volunteered for the fight against Germany. This resulting volume offers a vivid account of the physical and emotional experiences of seventeen British soldiers whose letters survive. Drawn from different regiments, social backgrounds, and areas of England and Scotland, they include twelve officers and five ordinary "Tommies." Â The book explores the training, journey to France, fear, shellshock, and life in the trenches as well as the leisure, love, and home leave the soldiers dreamed of. Fletcher discusses the psychological responses of 17- and 18-year-old men facing appalling realities and considers the particular pressures on those who survived their fallen comrades. While acknowledging the horror and futility the soldiers of the Great War experienced, the author shows another side to the story, focusing new attention on the loyal comradeship, robust humor, and strong morale that uplifted the men at the Front and created a powerful bond among them"--Publisher's description.
Going to war -- 'Quiet earnest faces': the national cause -- 'Glad to go': patriotic idealism -- 'Ready to go': training -- At the front -- 'Write as often as you can': letters and parcels -- 'Sticking it out': fear and shell shock -- 'A certain sense of safety with him': leadership -- 'Such a hopeless lot of babes': care for the men -- 'Drops of his blood on my hand': horror and endurance -- 'I merely did my duty': discipline and morale -- 'Very gallant in every way': early losses -- 'Blighty, oh blighty in about a week': leave -- 'I am serene, unafraid': the Somme -- 'Capable of finishing the job': battles of 1917-1918 -- 'The men cannot grasp it': armistice -- Sacrifice -- 'We will remember them': remembrance and commemoration -- 'All the best and choicest and unblemished': war heroes -- 'Among the happiest years I have every spent': survivors -- The Great War in perspective.
Print version record.
English.
Includes bibliographical references (pages 315-318) and index.
eBooks on EBSCOhost
Keywords: Great Britain. -- Army -- History -- World War, 1914-1918.; Great Britain. -- Army -- Military life -- History -- 20th century; Great Britain. -- Army. -- British Expeditionary Force; Grande-Bretagne. -- Army -- Vie militaire -- Histoire -- 20e siècle.; Great Britain. -- Army; Great Britain. -- Army. -- British Expeditionary Force; World War, 1914-1918 -- Social aspects -- Great Britain; World War, 1914-1918 -- Social aspects -- Europe, Western; World War, 1914-1918 -- Personal narratives, British; Soldiers -- Great Britain -- Correspondence; Guerre mondiale, 1914-1918 -- Aspect social -- Grande-Bretagne.; Guerre mondiale, 1914-1918 -- Aspect social -- Europe de l'Ouest.; HISTORY -- Europe -- Western; HISTORY -- Modern -- 20th Century; Armed Forces -- Military life; Social aspects; Soldiers; Western Europe; Great Britain; 1900-1999; Electronic book; History; Personal narratives; Personal correspondence